Genome re-sequencing and functional analysis places the Phytophthora sojae avirulence genes Avr1c and Avr1a in a tandem repeat at a single locus. - Ren Na; Dan Yu; B Patrick Chapman; Yun Zhang; Kuflom Kuflu; Ryan Austin; Dinah Qutob; Jun Zhao; Yuanchao Wang; Mark Gijzen (PLoS ONE)
The aim of this work was to map and identify the Phytophthora sojae Avr1c gene. Progeny from a cross of P. sojae strains ACR10×P7076 were tested for virulence on plants carrying Rps1c. Results indicate that avirulence segregates as a dominant trait. We mapped the Avr1c locus by performing whole genome re-sequencing of composite libraries created from pooled samples. Sequence reads from avirulent (Pool1) and virulent (Pool2) samples were aligned to the reference genome and single nucleotide polymorphisms (SNP) were identified for each pool. High quality SNPs were filtered to select for positions where SNP frequency was close to expected values for each pool. Only three SNP positions fit all requirements, and these occurred in close proximity. Additional DNA markers were developed and scored in the F₂ progeny, producing a fine genetic map that places Avr1c within the Avr1a gene cluster. Transient expression of Avr1c or Avr1a triggers cell death on Rps1c plants, but Avr1c does not trigger cell death on Rps1a plants. Sequence comparisons show that the RXLR effector genes Avr1c and Avr1a are closely related paralogs. Gain of virulence on Rps1c in P. sojae strain P7076 is achieved by gene deletion, but in most other strains this is accomplished by gene silencing. This work provides practical tools for crop breeding and diagnostics, as the Rps1c gene is widely deployed in commercial soybean cultivars.